A Comparison of the National Security and the Cybersecurity Approaches of the United States under Presidents Trump and Bidenversus the National Security and Cybersecurity Approach of Canada - Donald L. Buresh (Journal of Business Management and Economics, 2021)
The paper compares the national security and cybersecurityapproaches of the United States under President Trump and President Biden versus the national security and cybersecurity approach of Canada. The four pillars of the American national security strategy are outlined, and then the five pillars of America’s cybersecurity strategy are examined. Biden administration’s approach to national security and cybersecurity is also discussed. The Canadian approach to national security is highlighted, followed by a treatment of the Canadian cybersecurity strategy. The two national security strategies are compared, followed by contrasting the American versus the Canadian cybersecurity strategies. Although both nations are dedicated to protecting their citizens, Canada is less concerned about preserving the Canadian way of life than the United States. The American national cybersecurity strategy appears to be cloaked in the language of unification, whereas the Canadian approach to national security seems to be focused on practical strategic considerations. The United States’ national security is motivated to preserve peace through strength, while Canada promotes its national security via cooperation and collaboration. The conclusion is that the divergence between the strategies is due more to cultural differences than to a difference in technical approaches.